2017
DOI: 10.7717/peerj.4065
|View full text |Cite
|
Sign up to set email alerts
|

NDUFA4L2 is associated with clear cell renal cell carcinoma malignancy and is regulated by ELK1

Abstract: BackgroundClear cell renal cell carcinoma (ccRCC) is the most common and lethal cancer of the adult kidney. However, its pathogenesis has not been fully understood till now, which hinders the therapeutic development of ccRCC. NADH dehydrogenase (ubiquinone) 1 alpha subcomplex 4-like 2 (NDUFA4L2) was found to be upregulated and play an important role in ccRCC. We aimed to further investigate the underlying mechanisms by which NDUFA4L2 exerted function and its expression level was upregulated.MethodsThe Gene Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…Furthermore, NDUFA4L2 overexpressed was reported to be associated with renal clear cell carcinoma malignancy. And its expression was regulated by ELK1 in renal clear cell carcinoma cells [ 25 ]. Combined with the above outcomes, we could suppose that SHMT2 and its co-expressed gene NDUFA4L2 may modulate the initiation and development of kidney cancer and influence its prognosis, which may serve as the potential targets for kidney cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, NDUFA4L2 overexpressed was reported to be associated with renal clear cell carcinoma malignancy. And its expression was regulated by ELK1 in renal clear cell carcinoma cells [ 25 ]. Combined with the above outcomes, we could suppose that SHMT2 and its co-expressed gene NDUFA4L2 may modulate the initiation and development of kidney cancer and influence its prognosis, which may serve as the potential targets for kidney cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, KRAS or ELK1 overexpression inhibited the sensitivity enhancement of HeLa CR Cells to cisplatin which was induced by tanshinone I. ELK1 is one member of the ETS oncogene family of transcription activators in different human tumors, and many studies showed that downregulated ELK1 expression has antitumor activities against various type of cancer. For instance, Wang et al reported that elevated expression of NDUFA4L2 had positive correlation with clear cell renal cell carcinoma malignancy and was modulated by ELK1 . Zhang et al demonstrated that miR‐326 had suppressive activities on cervical cancer via targeting ELK1 .…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, eight of the top 10 genes in the differential gene network of KIRC except C3 and C4A have been reported to be implicated in renal cell carcinoma (RCC). Specifically, NDUFA4L2 is overexpressed in clear cell RCC (ccRCC); its mRNA level is correlated with tumor stage and overall survival time [50, 51]; and the association of NDUFA4L2 with ccRCC is regulated by ELK1 [52]. UMOD expression is downregulated in RCC [53, 54], and the homozygous genotype of UMOD is associated with more aggressive RCC [55].…”
Section: Discussionmentioning
confidence: 99%